PENGARUH REPUTASI DALAM HUBUNGAN ANTARA ASIMETRI INFORMASI DENGAN SENJANGAN ANGGARAN DIBAWAH METODE KOMPENSASI TRUTH INDUCING - Shofiana Brahmayanti; Mahfud Sholihin (Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
Previous studies suggest that reputation affects the relationship between information asymmetry and budgetary slack under the” slack inducing” compensation scheme. This current study examines whether the same effect occurs under the “truth inducing” compensation scheme. Using between subject experimental design, this study finds that reputation affect the relationship between information asymmetry and budgetary slack under the truth inducing compensation scheme. Especially, the results indicate that high reputation decreases budgetary slack when information asymmetry exists. The results may provide contributions both for theory development and practical implication